The effect of peer-mediated learning strategy and gender on polytechnic students’ mastery of keyboarding skills in Osun State, Nigeria - Olafare, Elkanah Ayodeji; Jimoh, Abiodun Ganiu; Ajayi, Bukola Julianah; Abanyam, Friday Ekahe (International Business Education Journal, 2025)
This study investigated the effect of peer-mediated strategy on polytechnic students’ mastery of keyboarding skills in Osun State, Nigeria. A quasi-experimental design was used for the study with a 2x2 factorial matrix. The population of the study comprised two hundred and forty-three (243) National Diploma (ND) I Office Technology and Management students in all Polytechnic in Osun State. A total of 140 students in their intact classes was used as the sample for the study. Keyboarding Skill Test (0.89) was the instrument validated and used for data collection. Data collected were analysed using mean and standard deviation to answer the research questions and Analysis of Covariance (ANCOVA) to test the hypotheses at the 0.05 level of significance. The study revealed that there was a significant effect of treatment (with a peer-mediated strategy) on students’ mastery of keyboarding skills (F-value = 872.352, p < 0.00) because students taught with peer-mediated performed better than those taught using the conventional demonstration method (mean gain of 26.417 & 22.090 > 4.426). There was a significant effect of gender on students’ mastery of keyboarding skills in the polytechnic (F-value = 103.897, p < 0.05). The result also showed a significant interaction effect of treatments and gender on students’ mastery of keyboarding skills (F-value = 49.992, p < 0.05). The study concluded that peer-mediated strategy is more effective in enhancing students’ mastery of keyboarding skills in polytechnic than the conventional method. Based on the foregoing, it was recommended that Office Technology and Management (OTM) instructors in polytechnics should employ the use of a peer-mediated strategy for keyboarding instructional delivery.